2020
DOI: 10.1038/s41467-020-16775-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between ambient temperature and hypertensive disorders in pregnancy in China

Abstract: Hypertensive disorders in pregnancy (HDPs) are leading perinatal diseases. Using a national cohort of 2,043,182 pregnant women in China, we evaluated the association between ambient temperatures and HDP subgroups, including preeclampsia or eclampsia, gestational hypertension, and superimposed preeclampsia. Under extreme temperatures, very cold exposure during preconception (12 weeks) increases odds of preeclampsia or eclampsia and gestational hypertension. Compared to preconception, in the first half of pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 47 publications
0
37
1
2
Order By: Relevance
“…In Brazil, Melo et al observed that gestational hypertension increased significantly during the colder months, especially in August when the southern hemisphere is in winter [ 17 ]. A recent study from China found that exposure to very cold weather before pregnancy increased the risk of preeclampsia, eclampsia and gestational hypertension; and conversely, exposure to cold in the first half of pregnancy reduces, while hot weather increases the risk of hypertensive disorders in pregnancy [ 64 ]. But, Elongi et al found no association between gestational hypertension and seasonal changes, during their 36-month study, in Mississippi [ 65 ], which is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Melo et al observed that gestational hypertension increased significantly during the colder months, especially in August when the southern hemisphere is in winter [ 17 ]. A recent study from China found that exposure to very cold weather before pregnancy increased the risk of preeclampsia, eclampsia and gestational hypertension; and conversely, exposure to cold in the first half of pregnancy reduces, while hot weather increases the risk of hypertensive disorders in pregnancy [ 64 ]. But, Elongi et al found no association between gestational hypertension and seasonal changes, during their 36-month study, in Mississippi [ 65 ], which is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation was that the pregnant women in this study cohort were generally younger than 35 years old; therefore, research on FGF21 in GDM women over 35 years old still needs to be performed. However, studies have shown that pregnant women younger than 35 years old account for more than 85% of the total number of pregnant women in China ( 41 ). Therefore, the findings of this study are still very instructive and interesting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extreme heat exposure during pregnancy affects glucose metabolism and increases insulin resistance, leading to gestational diabetes [16][17][18]. Moreover, some evidence indicates that elevated temperature causes maternal hypertension, especially pre-eclampsia, one of the main risk factors for global maternal mortality [19].…”
Section: Introductionmentioning
confidence: 99%